2015
DOI: 10.2460/javma.247.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood lactate concentration with physical perfusion variables, blood pressure, and outcome for cats treated at an emergency service

Abstract: Findings indicated that blood lactate concentration, together with physical examination findings and SAP, may be a useful tool for identifying abnormalities in tissue oxygen delivery in cats. However, lactate concentrations were not associated with outcome in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 20 publications
2
30
1
Order By: Relevance
“…The normalization of lactate concentration has not been shown to be associated with prognosis in cats with various critical illnesses . In the same report, cats with severe shock, quantified by having pale mucous membranes, abnormal peripheral pulse quality, and hypothermia, had a higher lactate concentration at presentation . In the present study, cats with SP may have a multifactorial explanation for their hyperlactatemia, namely decreased oxygen delivery due to a state of shock, variable organ derangements, as well as mitochondrial dysfunction due to sepsis.…”
Section: Discussionmentioning
confidence: 41%
“…The normalization of lactate concentration has not been shown to be associated with prognosis in cats with various critical illnesses . In the same report, cats with severe shock, quantified by having pale mucous membranes, abnormal peripheral pulse quality, and hypothermia, had a higher lactate concentration at presentation . In the present study, cats with SP may have a multifactorial explanation for their hyperlactatemia, namely decreased oxygen delivery due to a state of shock, variable organ derangements, as well as mitochondrial dysfunction due to sepsis.…”
Section: Discussionmentioning
confidence: 41%
“…Presently, there are few highly powered, large‐scale studies in the veterinary literature on which to base recommendations for using [LAC] measurements in patient evaluation and management. In an effort to provide some general guidelines, a literature search of PubMed, Scopus, and CAB Abstracts performed for this review identified 35 clinical studies that investigated [LAC] as a prognostic indicator in dogs and cats . As in the human medical literature, there was marked heterogeneity in study sizes, study populations, mortality, and selected lactate cut‐off points making comparison across studies challenging.…”
Section: Lactate As a Prognostic Indicatormentioning
confidence: 99%
“…Cats with [LAC] >4.0 mmol/L and a decrease of ≥30% within 8 hours of admission had a higher survival (9/10: 90%) than those where [LAC] decreased <30% (1/6: 17%). In 111 cats presenting to an ED, 123 sick cats hospitalized for emergency care, and in 51 cats with septic peritonitis, [LAC] was not significantly different between nonsurvivors and survivors. In contrast, in 26 cats with septic peritonitis and in 600 cats admitted to an ICU, nonsurvivors had significantly higher [LAC] compared to survivors .…”
Section: Catsmentioning
confidence: 99%
“…There are fewer studies evaluating the prognostic utility of lactate in cats. In contrast to many studies in people and dogs, a recent study reported that emergency room admission lactate concentration was not significantly different between cats that did or did not survive to hospital discharge …”
Section: Introductionmentioning
confidence: 99%